Nano and Microbubble Systems for On-Demand Cancer Drug Delivery - Budhwani, Karim I.; Dettmann, Makena A.; Saleh, Mansoor N.; Thomas, Vinoy (Current Nanoscience, 2018)
Background: Chemotherapy, the predominant cancer treatment modality, suffers from elimination in renal and hepatic systems causing reduced bioavailability and increased toxicity leading to harmful side effects. Targeted release of formulations encapsulated in protective biocompatible polymer or polymer-lipid microbubbles can improve bioavailability and potency while reducing systemic toxicity, resulting in a higher therapeutic index. Objective: Double emulsion, the most common method for microbubble fabrication suffers from low encapsulation efficiency and wide size distributions. In this concise article, we analyze the emergent coaxial electrospray technique vis-is established double emulsion methods to manufacture biocompatible polymer microbubbles for targeted drug delivery systems. Method: Specifically, we investigate size, morphology, and encapsulation efficiencies of microbubbles fabricated using double emulsion and coaxial electrospray techniques. Results: We found that microbubbles produced via coaxial electrospray displayed higher encapsulation efficiency and a narrower size distribution. Conclusion: Coaxial electrospray is a promising technology with considerably improved size distribution and encapsulation efficiency; however, reproducibility across facilities and scale remain challenging.
Keywords: double emulsion